Vitrification of day 5/6 human morulas/blastocysts: A 10 year retrospective study in a private assisted reproductive techniques [ART] clinic - Wilson Poe, Emma (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2015.